Promising biomolecules - Oliveira, Isabel M. (2018)
The osteochondral defect (OD) comprises the articular cartilage and its subchondral bone. The treatment of these lesions remains as one of the most problematic clinical issues, since these defects include different tissues, requiring distinct healing approaches. Among the growing applications of regenerative medicine, clinical articular cartilage repair has been used for two decades, and it is an effective example of translational medicine; one of the most used cell-based repair strategies includes implantation of autologous cells in degradable scaffolds such as alginate, agarose, collagen, chitosan, chondroitin sulfate, cellulose, silk fibroin, hyaluronic acid, and gelatin, among others. Concerning the repair of osteochondral defects, tissue engineering and regenerative medicine started to design single- or bi-phased scaffold constructs, often containing hydroxyapatite-collagen composites, usually used as a bone substitute. Biomolecules such as natural and synthetic have been explored to recreate the cartilage-bone interface through multilayered biomimetic scaffolds. In this chapter, a succinct description about the most relevant natural and synthetic biomolecules used on cartilage and bone repair, describing the procedures to obtain these biomolecules, their chemical structure, common modifications to improve its characteristics, and also their application in the biomedical fields, is given.